Daya pikir kritis pemelajar BIPA 4 dalam penilaian keterampilan berbicara berkonteks sosiokultural - Ananda Siti Khoirunnisa; Isah Cahyani; Vismaia S. Damayanti (Badan Pengembangan dan Pembinaan Bahasa, 2023)
Critical thinking skills can help BIPA learners improve their speaking competence. BIPA teachers need to stimulate learners' critical thinking by using sociocultural context. This study aims to address the need for stimulating learners' critical thinking in responding to sociocultural contexts. The research method used is descriptive-qualitative. The data source for this study is the performance assessment results of four BIPA level 4 learners. The findings of this study indicate that the average learner’s final score in the speaking assessment is 89. The acquisition of this final score indicates that the sociocultural context in BIPA evaluation can stimulate critical thinking for learners to express their opinions in speaking. Learners' critical thinking is reflected in the preparation of performance assessment, idea processing, and delivery of the speech context. Furthermore, this research can serve as an initial study to enhance learners' critical thinking skills in BIPA learning.